Technology and diversity in higher education new challenges - Inoue, Yukiko; Gale Group (Hershey, Penn. Information Science Pub., 2007)
"This book examines current and effective educational practices as well as new challenges involving emerging technologies in increasingly diverse learning environments in higher education and the impact of the explosion of technology. These challenges are well documented in this collection of essays, case studies, and research reports"--Provided by publisher.
Foreword -- Preface -- Section I: Literary reading and technology -- Section II: Case studies in technology and diversity -- Section III: Evaluating the role and impact of technology in medical education -- Section IV: Questionnaire research in technology and diversity -- Section V: Development and implementation of technology and diversity in learning -- Section VI: Opportunities and new challenges in technology and diversity -- About the authors -- Index.
Electronic reproduction.
Keywords: Education, Higher -- Computer-assisted instruction; Educational technology; Electronic books